A Flexible DNA Biosensor for Breast Cancer Marker BRCA1 Detection. Issue 48 (28th December 2020) - Wang, Qi; Zhang, Huanyu; Shen, Xiaohui; Wang, Fenghe; Mao, Chun
Abstract: Early detection of breast cancer is of great significance to improve the prognosis and survival rate of breast cancer. However, how to detect breast cancer 1 gene mutation (BRCA1) efficiently in early stage is still a great challenge. In the past few decades, more and more attention has been paid to the design of a biosensor. In this work, A method for rapid detection of specific BRCA1 using silver nanowires modified polyethylene terephthalate (PET) film as a disposable electrode was proposed. With a high aspect ratio, AgNWs distributed in the PET film were easy to form a conductive network as a flexible electrode. A well‐conductive gold sputtering layer can prevent AgNW from falling off to provide a conductive and stable electrode substrate. The Au‐HRP can effectively reflect the hybridization matching phenomenon of target. Results indicated this strategy we proposed had a low detection limit with different concentrations of complementary DNA with limit of detection of 5.3×10 −15  M in the range from 5.0×10 −10  M to 5.0×10 −7  M. Due to the high sensitivity, simplicity and cheap price, arbitrary cut, AgNWs/PET film becomes a promising electrode material for quantification of low concentration biological component in early diagnosis. Abstract : A flexible DNA biosensor was reported composed of silver nanowires decorated‐polyethylene terephthalate (AgNWs/PET) film as a disposable and flexible electrode for the rapid detection of specific BRCA1. This strategy we proposed showed a low detection limit (5.3×10 −15  M) and wide detection range (5.0×10 −10  M to 5.0×10 −7  M). Therefore, AgNWs/PET film becomes a promising electrode material for quantification of low concentration biological component in early diagnosis.